Practice and Exploration of Ideological and Political Education Reform in Course of Modern Food Testing Technology - Fang, Yishan; Chen, Huiyi; Tao, Haiteng; Tian, Ying; Lu, Lu; Cui, Bo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Based on the new era, “curriculum ideology and politics” as the mainstream advanced educational concept is the focus of teaching reform in higher education institutions. The rapid development of the food industry has put forward higher requirements for “three comprehensive education”. Modern food testing technology, as a fundamental course in the food industry, includes rich knowledge of detecting food through modern technological means, while the course contents also contain rich ideological and political factors, and occupies an important position in China's food discipline. With moral education as the core, it comprehensively promotes the construction of ideological and political courses and meets the high-quality training of high-quality talents, which is the top priority of teaching reform. This study adopts descriptive, qualitative research methods and mixed approach, collecting data through practical operations, interview techniques, and literature review. This analysis utilized continuous participatory techniques, including stages of observation, practice, interviews, case studies, focus group discussions and literature research, presentation, and drawing conclusions. In view of the current practice and exploration, this article extracts the commonalities between science and engineering courses and ideological and political education for integration to break the singularity of teaching practice. At the same time, it constructs a “three in one” collaborative education mechanism to enhance the organic integration of ideological and political education and curriculum teaching, in order to achieve the goal of inheriting the past and opening up the future. By introducing the significance and construction strategies of ideological and political education in the course of Modern Food Testing Technology, this article aims to provide suggestions and references for the reform of ideological and political education in relevant courses in universities.